Prevalence of Hearing Loss and Associated Factors in School-Age Individuals in an Urban Area of Northeast Brazil - Nunes, Aryelly Dayane Silva; Balen, Sheila Andreoli; Souza, Dyego Leandro Bezerra; Barbosa, Isabelle Ribeiro (International Archives of Otorhinolaryngology, 2020)
Introduction Hearing loss interferes in the development of language and verbal capacities, which causes learning difficulties and deleterious effects.Objective To analyze the prevalence and associated factors for hearing loss in school-age individuals of the municipality of Natal, state of Rio Grande do Norte, Northeast Brazil.Methods Cross-sectional study that evaluated 238 school-age individuals (6–17 years old) in municipal public schools. Meatoscopy was performed and school-age individuals answered the questions “Do you think that you hear well?” and “Do you have earaches?”. Auditory evaluation was performed with a Telessaúde audiometer. The responsible adults answered socioeconomic, speech and audiology aspects and risk factors for hearing loss questionnaire.Results The prevalence of hearing loss was 16% (11.7–21.4%); 16% reported not to hear well, 18.9% reported earaches, and 26.1% presented altered meatoscopy. The prevalence of hearing loss was higher in school-age individuals who reported hearing difficulties, in children between the ages of 6 and 12, and with altered meatoscopy results (p < 0.05). Airway infection (PR = 3.37; 95% confidence interval [CI]: 1.48–7.68) was found as a risk factor associated with hearing loss, remaining significant in the multivariate model (PR = 6.79; 95%CI: 1.98–23.26; p = 0.002).Conclusions Hearing loss in this sample is above the values reported in other studies performed in Brazil for this age group. This highlights the necessity of better structure of speech and audiology attention, so that auditory health promotion actions can be systematized for this population.
Keywords: hearing loss; child; adolescent; prevalence; epidemiological factors